2020
DOI: 10.1007/s11356-019-07366-2
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of chlordecone environmental availability by soil amendment of biochars and activated carbons from lignocellulosic biomass

Abstract: Chlordecone (kepone or CLD) was formerly used in French West Indies as an insecticide. Despite its formal ban in 1993, high levels of this pesticide are still found in soils. As such, sequestering matrices like biochars or activated carbons (ACs) may successfully decrease the bioavailability of halogenated compounds like CLD when added to contaminated soils. The present study intends (i) to produce contrasted sequestering matrices in order to (ii) assess their respective efficiency to reduce CLD environmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 46 publications
3
23
1
Order By: Relevance
“…For AC materials, AC2 and AC3 were the most effective in reducing PCB concentrations given their larger specific surface area and mesoporous surface, while AC1 was less effective due to its granular shape. This result confirms that surface properties and textural characteristics impact the sorption properties of carbonaceous materials in contaminated soils [11,12,14,26,27]. Regarding the type of pollutants, no difference could be shown in terms of sequestration efficiency by the different carbonaceous materials probably because the physicochemical properties related to adsorption in soil such as lipophilicity are of the same order (about log Kow of 7).…”
Section: In Vitro Assessment Of Interactions Between Pollutants and C...supporting
confidence: 71%
See 2 more Smart Citations
“…For AC materials, AC2 and AC3 were the most effective in reducing PCB concentrations given their larger specific surface area and mesoporous surface, while AC1 was less effective due to its granular shape. This result confirms that surface properties and textural characteristics impact the sorption properties of carbonaceous materials in contaminated soils [11,12,14,26,27]. Regarding the type of pollutants, no difference could be shown in terms of sequestration efficiency by the different carbonaceous materials probably because the physicochemical properties related to adsorption in soil such as lipophilicity are of the same order (about log Kow of 7).…”
Section: In Vitro Assessment Of Interactions Between Pollutants and C...supporting
confidence: 71%
“…A possible strategy to reduce this halogenated POP transfer to vegetal is to trap them in the soil by making them non-available. In this perspective, several amendment materials have already been evaluated and proven to be effective to limit the POP transfer, as assessed on root vegetables [9,10] or through an in vitro assay [11,12]. To limit transfer to plant, compost amendment of chlordecone (CLD) contaminated soils displayed a reduction of transfer to root vegetables by a factor of 3 to 10 compared to non-amended soils [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To face this situation, soil remediation programs have been proposed since soil is the main source of contamination of all the other FWI ecological compartments. Some of these programs suggest adding CLD adsorbents to the soil (activated carbon, biochar, compost) to decrease or eliminate CLD transfers to water, crops, and breeding animals (Clostre et al 2014b;Ranguin et al 2020), to extract CLD from soil with plants (Liber et al 2018) or to destroy CLD by microbial or physicochemical processes (Chevallier et al 2019;Lomheim et al 2020;Macarie et al 2016;Mouvet et al 2017). To date, among all these approaches, beside the addition of compost, the physicochemical In Situ Chemical Reduction (ISCR) process, which consists of adding Fe 0 to the soil, is the only one to have been tested with some success under real environmental conditions in FWI, up to the plot scale (Mouvet et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…One possible strategy to reduce this CLD transfer to animals is to sequestrate it within the soil matrix. In this perspective, several amendment sources have already been evaluated and proven to be effective to limit the CLD transfer, as assessed using plants (Fernandes et al, 2010;Woignier et al, 2015Woignier et al, , 2012 or through an in vitro assay (Ranguin et al, 2020) and confirmed in animal studies using artificial soils (Delannoy et al, 2019;. To limit transfer to plant, compost amendment of CLD-contaminated soils displayed a reduction of transfer to plants by a factor of 3 to 10 compared to non-amended soils (Woignier et al, 2012).…”
Section: Introductionmentioning
confidence: 99%